{Fertility awareness and intentions among young adults in Greece.} - Lardou, Ioanna; Chatzipapas, Ioannis; Chouzouris, Michail; Xenos, Panos; Petrogiannis, Nikolaos; Tryfos, Dimitrios; Chandakas, Stephanos; Grigoriadis, Themos; Michala, Lina (Upsala journal of medical sciences, 2021)
BACKGROUND: Greece has a mean age of first motherhood at 31.5 years, higher than the European average age of 29.4. Delaying conception, however, may be an important non-reversible cause of infertility. The aim of this study was to identify possible knowledge deficits regarding fertility in young adults. METHODS: This was an online survey of young adults, regarding information on intention to parenthood and knowledge on issues affecting fertility. This study was conducted from February to December 2020, aiming for a representative sample of Greek men and women aged 18 and 26 years. The questionnaire was designed by a multidisciplinary group based on the Cardiff Fertility Knowledge Scale, which contained 22 multiple-choice or Likert-scale questions. RESULTS: We obtained responses from 1875 young adults, whose mean age was 22.1 years. About 91.8{%} of men and 94.0{%} of women declared an intention to have children, out of which 44.0{%} wanted to have two and 29.0{%} three children. About 52.0 and 50.8{%} men and women, respectively, aimed to start a family between 31 and 35 years. Residents of rural areas and those with a lower education level more likely aimed to have children before the age of 30. The most prevalent answers for age of ideal parenthood were between 26 and 30 years for a woman and 31-35 years for a man. Smoking, alcohol consumption and sexually transmitted infections were identified as factors affecting both female and male fertility. Half of men and women, respectively, overestimated general success rates of reproductive techniques. CONCLUSION: The knowledge of fertility, particularly with regards to assisted reproductive techniques' success rates, may be overestimated as more young adults plan for having children after the age of 30.
Keywords: Adolescent; Adult; Attitudes; Child; Epidemiology; Female; Fertility; Greece; Health Knowledge; Humans; infertility; Intention; Male; Practice; Young Adult